SENYAWA PENYUSUN EKSTRAK FLAVOR DAUN SALAM (Eugenia polyantha Wight) HASIL DISTILASI UAP MENGGUNAKAN PELARUT N-HEKSANA DAN TANPA N-HEKSANA - Wartini, Ni Made (Agrotekno, 2009)
The aim of research is to determine the composition offlavour extracts of salam leaf obtained from steamdistillation method using n-hexane and no n-hexane. Freshsalam leaves were cut and extracted using steam distillationmethods and the flavour extract was drying by addingMgSO4 anhydrate. The flavour extracts were analyzed byemploying gas chromatography-mass spectrometry (GCMS).The research results indicated as the following: 1) theflavour extracts obtained by steam distillation without nhexane,contained 27 compounds. The main compoundswere cis-4-decenal (27.12%), octanal (11.98%), ?-pinene(9.09%), farnesol (8.84%), ß-ocimene (7.62%) and nonanal(7.60%), 2) the flavour extracts yielded from steamdistillation using n-hexane, contained 26 compounds. Themain compounds are cis-4-decenal (18.74%), octanal(6.97%), ?-pinene (9.09%), farnesol (16.95%), nerolidol(4.09%) and decanal (3.14%).